Strengthening of Reinforced Concrete with Steel Fibre: A Review - Solahuddin, B. A. (Trans Tech Publications Ltd., 2022)
Cement, sand, aggregate, water and reinforcing bar are the materials in reinforced concrete, while a mixture without reinforcing bar is known as concrete. Concrete and reinforced concrete is the most widely used building material in the construction industry. Brittleness occurs when concrete is unable to withstand tensile loading, resulting in brittle failure. Moreover, fibre has the potential to improve the tensile strength of concrete. Due to this fact, steel fibre reinforced concrete (SFRC) exhibits superior resistance to cracking. It intends to increase the durability and decrease the crack deformation characteristics. This review article discusses the theoretical aspects of SFRC. Numerous references from both early and contemporary writers are included to help tie the subject together chronologically. This historical analysis aims to provide context for what is currently known about SFRC rather than to provide historical reporting. Hence, this paper discusses a review on the strengthening of reinforced concrete with steel fibre based on previous research before this.